2007
DOI: 10.1007/s10802-007-9177-5
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Relationships and ADHD Symptoms: A Longitudinal Analysis

Abstract: Evidence both from psychological research and clinical intervention studies suggests that there are bidirectional influences between overt child behavior problems and parent-child relations. Very little research however, has considered the pattern of relations that exists between Attention Deficit Hyperactivity Disorder (ADHD) and the parent-child relationship within a longitudinal context. Using a longitudinal community sample from the United Kingdom which included 194 school aged children (46% male and 54% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 53 publications
6
116
3
4
Order By: Relevance
“…Because mothers are the primary caregivers, they may spend more time with their sons and daughters than fathers do, thereby increasing the likelihood of discussions that might become conflicts The finding that among adolescents with ADHD there were no differences in the number of conflicts between mothers versus fathers is not likely due to fathers of youth with ADHD spending more time with their sons or daughters. Research shows that fathers of children with ADHD are more avoidant and less involved in childcare than mothers (Arnold, O'Leary, & Edwards, 1997;Lifford, Harold, & Thapar, 2008). Results of the present study, however, showed that fathers of adolescents with ADHD were more likely to report having conflicts about adolescents coming home on time, and talking back to parents than fathers in the comparison group.…”
Section: Number Of Conflictscontrasting
confidence: 87%
See 1 more Smart Citation
“…Because mothers are the primary caregivers, they may spend more time with their sons and daughters than fathers do, thereby increasing the likelihood of discussions that might become conflicts The finding that among adolescents with ADHD there were no differences in the number of conflicts between mothers versus fathers is not likely due to fathers of youth with ADHD spending more time with their sons or daughters. Research shows that fathers of children with ADHD are more avoidant and less involved in childcare than mothers (Arnold, O'Leary, & Edwards, 1997;Lifford, Harold, & Thapar, 2008). Results of the present study, however, showed that fathers of adolescents with ADHD were more likely to report having conflicts about adolescents coming home on time, and talking back to parents than fathers in the comparison group.…”
Section: Number Of Conflictscontrasting
confidence: 87%
“…Results of the present study showed that adolescents with ADHD reported more conflict with both parents in spite of the fact that they seem to spend less time with fathers than with mothers (Arnold et al, 1997). Furthermore, fathers of children with ADHD are more avoidant and less involved in childcare than mothers (Lifford et al, 2008). Perhaps the attributions of adolescents with ADHD did not predict conflict with their fathers because adolescents may perceive that fathers do not know enough about their everyday issues and are not as involved and supportive as mothers.…”
Section: Adolescent-reported Attributions For Conflict With Fatherscontrasting
confidence: 44%
“…Although parenting behaviors may elicit ADHD-type behaviors, the possibility of 'child effects' also merits consideration in our understanding of directionality for ADHD in older children. Attention problems at age 12 years predicted mother-child rejection assessed at a 1-year follow-up, even after controlling for initial mother-child rejection (Lifford et al, 2008). Children with ADHD may be more likely to elicit negative or harsh parenting, as parents with children with ADHD are significantly more likely to use corporal punishment compared with parents of children without ADHD (Alizadeh et al, 2007), thus, risk for abuse may be higher among children with ADHD.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 96%
“…However, when comparing the perceptions of rejection/acceptance between parents and children of the ADHD group, adults scored higher on both. In relation to acceptance, the data is indeed negative, as the emotional and behavioral development of children with ADHD is mediated by external variables such as perceived acceptance or rejection of their family (Lifford, Harold, & Thapar, 2008;Murris, Meesters, & Van der Berg, 2003;Shaw, et al, 1998). While we need to be aware that this conclusion is mediated by the fact that perceptions of children with ADHD, obtained through self-reports, may be distorted by their disorder (Bauermeister, et al 2005;Walcott & Landau, 2004), this is something that should be monitored in the future.…”
Section: Resultsmentioning
confidence: 99%